Advance of microfluidic constriction channel system of measuring single‐cell cortical tension/specific capacitance of membrane and conductivity of cytoplasm. Issue 5 (25th November 2021) - Liu, Yan; Wang, Ke; Sun, Xiaohao; Chen, Deyong; Wang, Junbo; Chen, Jian
Abstract: This paper reported a microfluidic platform which realized the characterization of inherent single‐cell biomechanical and bioelectrical parameters simultaneously. Individual cells traveled through a constriction channel with deformation images and impedance variations captured and processed into cortical tension T c, specific membrane capacitance C sm, and cytoplasmic conductivity σ cy based on an equivalent biophysical model. These properties of thousands of individual cells of K562, Jurkat, HL‐60, HL‐60 treated with paraformaldehyde (PA)/cytochalasin D (CD)/concanavalin A (ConA), granulocytes of Donor 1, Donor 2, and Donor 3 were quantified for the first time. Leveraging T c, C sm, and σ cy, (1) high accuracies of classifying wild‐type and processed HL‐60 cells (e.g., 93.5% of PA treated vs. CD treated HL‐60 cells) were realized, revealing the effectiveness of using these three biophysical parameters in cell‐type classification; (2) low accuracies of classifying normal granulocytes from three donors (e.g., 56.4% of Donor 1 vs. 2), indicating comparable parameters for normal granulocytes. In conclusion, this platform can characterize single‐cell T c, C sm, and σ cy concurrently and quantify multiple parameters in single‐cell analysis.